PP15 Bioremoval of Doxycycline in aqueous media by encapsulation of the microalga Chlorella vulgaris: a comparison with free and encapsulated microalgae - Peña Meneses, Celeste; Rosero Hoyos, María Camila; González Hurtado, Jennifer Vanessa; Hernández Blanco, Fernando José (Revista Productos Naturales, 2025)
Emerging contaminants, present in low concentrations in water, represent an environmental risk and lack complete regulation. Bioremoval using microalgae Chlorella vulgaris has demonstrated high efficiency, removing up to 98% of pharmaceuticals such as loratadine and diclofenac; for ease of handling, it was encapsulated in sodium alginate, achieving up to 90% removal. The current study analyzes the removal of doxycycline and evaluates a combined matrix of sodium alginate and sodium polyacrylate, this combination improved efficiency to 75–80%, demonstrating its potential to optimize bioremoval and facilitate the recovery of algal biomass in contaminated water.
Keywords: Emerging contaminants; Bioremoval; Microalgae